The Long-Run Labour Market Effects of the Canada-U.S. Free Trade Agreement - Kovak, Brian K; Morrow, Peter M (Review of Economic Studies, 2025)
Abstract This article assesses the long-run effects of the 1989 Canada-U.S. Free Trade Agreement on the Canadian labour market using matched longitudinal administrative data for the years 1984–2004. We simultaneously examine the labour market effects of increased export expansion and import competition, generally finding adverse effects of Canadian tariff cuts and favourable effects of U.S. cuts, though both effects are small. Workers initially employed in industries that experienced larger Canadian tariff concessions exhibit a heightened probability of layoffs at large firms, but little impact on long-run cumulative earnings. Lower earnings and years worked at the initial employer are offset by gains in other manufacturing industries, construction, and services. Canadian workers quickly transitioned out of industries facing import competition, with the bilateral nature of the FTA providing import-competing workers employment options in alternative manufacturing industries benefiting from larger U.S. tariff cuts.